A Learning Model Based on Doing Empowering and Facilitating to Improve Life Skills - Suranto Suranto; Munajat Tri Nugroho; Muhammad Fahmi Johan Syah; Adcharina Pratiwi (Jurnal Penelitian Pendidikan IPA, 2024)
This research formulates learning models to improve life skills through doing, empowering and facilitating (DEFI). The developed model puts affective, cognitive, and psychomotoric forward. The object of research is students of heavy equipment mechanic competence. Data collection is obtained through observation, interview, questionnaire, documentation and literature study. Quantitative and qualitative analysis methods for goodness of fit model are data analysis and experimental tests. The t-test value hypothesis is used to determine the average test group as a measure of the effectiveness of the model's work, and the resulting learning model model is effective in improving life skills.